BEHAVIOUR OF THE "ATHENIAN SCHIST" IN EXCAVATION BY AN OPEN FACE SHIELD BORING MACHINE. EXTENSION LINE TO PERISTERI OF THE METROPOLITAN RAILWAY OF ATHENS. - Μαρίνος Π.; Μαρίνος Β.; Στούμπος Γ.; Νόβακ M.; Κορκάρης K.; Μπενίση M. (Bulletin of the Geological Society of Greece, 2004)
The excavation of the Metropolitan Railway of Athens is being opening mainly through the system of "Athenian Schist" which basically is constituted by a sequence of schists and metasandstones and presents high heterogeneity and tectonic disturbance due to faults and shear zones. The excavation is either mechanized or conventional. This paper is focused on the extension line to Peristeri, where an OFS (Open Face Shield) ΤΒΜ was used. This machine is effective in controlling any instabilities in fair quality rock mass, but not when poor quality rock masses are present where the stand-up time is limited. In such cases immediate support of the face or even improvement of the quality of the material is necessary. In this paper a specific classification of "Athenian Schist" is described in order to provide predictions for the behaviour of the rock masses under the conditions of an excavation with an OFS and, to access the risks but also the need of remedial measures